The psychology of vampires - Cohen, David, 1946- author.
1 online resource (xvii, 136 pages).
Keywords: Why have vampires become such a feature of modern culture? Can vampire-like conditions be explained by medical research? Is there a connection between vampirism and Freud? The Psychology of Vampires presents a captivating look at the origins of vampires in myth and history, and the psychological theories which try to explain why they fascinate us. It traces the development of vampires from the first ever vampire tale, written by John Polidori in 1819, to their modern cultural legacy. Together with historical detail about Polidori's eventful life, the book also examines the characteristics of vampires, and explores how and why people might identify as vampires today. From sanguinarians who drink blood, to psychic vampires who suck the energy from those around them, The Psychology of Vampires explores the absorbing connections between vampirism and psychology, theology, medicine and culture.